Electronic stopping power correction for different phase shift conditions (Baghdad Science Journal, 2010)
Bloch correction is considered one of the important corrections for stopping power for its ability to connect the classic description of the (Bohr) scientist with the quantum treatment of (Bethe) scientist.In this research we made a study about considoving the Bloch correction a bout phase shift conditions and for different phases from particle energy and appeared that Bloch correction in its relativistic case and non- relativistic case that depend on phase shift condition and particle energy but in the Ultra relativistic case for Bloch correction that depend on phase shift condition only. We made electronic stopping power correction in low speed by using phase shift conditions .